33 Hen. 8, ch. 6 §§ 1, 2, 18 - (:unkn) unknown (General Publisher, 1541)
Prohibited possession of any crossbow, handgun, hagbutt, or demy hake. Exempted subjects living within 12 miles of the Scottish border. Punishable by forfeiture or payment of 10 pounds.
--
Keywords: POSSESSION